2021
DOI: 10.1016/j.bandl.2020.104880
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of brain plasticity supporting language recovery after perinatal arterial ischemic stroke

Abstract: Brain imaging methods such as functional Magnetic Resonance Imaging (fMRI) and Diffusion Tensor Imaging (DTI) have already been used to decipher the functional and structural brain changes occurring during normal language development. However, little is known about the differentiation of the language network after an early lesion. While in adults, stroke over the left hemisphere generally induces post-stroke aphasia, it is not always the case when a stroke occurs in the perinatal period, thus revealing a remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 101 publications
(117 reference statements)
1
8
0
1
Order By: Relevance
“…The finding that the RH auditory cortex can support speech perception aligns with reports of high-level language processing being successfully supported by the right hemisphere in some individuals with early left-hemisphere damage (Newport et al, 2022; Tuckute et al, 2022; see François et al, 2021 for a review). Such individuals develop linguistic abilities at the same time as their neurotypical peers and exhibit no language difficulties as adults.…”
Section: Discussionsupporting
confidence: 74%
“…The finding that the RH auditory cortex can support speech perception aligns with reports of high-level language processing being successfully supported by the right hemisphere in some individuals with early left-hemisphere damage (Newport et al, 2022; Tuckute et al, 2022; see François et al, 2021 for a review). Such individuals develop linguistic abilities at the same time as their neurotypical peers and exhibit no language difficulties as adults.…”
Section: Discussionsupporting
confidence: 74%
“…The injury of arcuate fiber bundles in specific functional language areas of the brain is the main factor leading to aphasia after stroke, which can also be used as an imaging auxiliary tool to evaluate the patient's condition [ 37 ]. François C. [ 38 ] found that patients with Broca aphasia, Wernicke aphasia, and conductive aphasia had different degrees of damage to the arcuate fiber bundle, and the damage location was related to the type of aphasia: Patients with Broca aphasia mainly had damage and displacement of the integrity of the front end of the arcuate fiber bundle, and patients with Wernicke aphasia mainly had middle and rear damage. In patients with conductive aphasia, the central part of the arcuate fiber bundle on the functional side was mainly damaged.…”
Section: Research Progress Of Dtimentioning
confidence: 99%
“…These may occur 24 h a day, making it difficult to distinguish foreground from background sounds at 60 db or to filter out and process noxious stimuli [36][37][38]. In this environment, the preterm infant is being deprived of the exposure to the human voice and speech, which is associated with the neurobiology of language development [39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%